Adverse effects of antipsychotic medication in patients with 22q11.2 deletion syndrome: A systematic review. Issue 11 (13th August 2019) - de Boer, Janna; Boot, Erik; van Gils, Lissa; van Amelsvoort, Therese; Zinkstok, Janneke
Abstract: The 22q11.2 deletion syndrome (22q11.2DS) is a multisystem condition and the most prevalent microdeletion syndrome in humans. Approximately 25% of individuals with 22q11.2DS receive antipsychotic treatment. To assess whether patients with 22q11.2DS are vulnerable to adverse effects of antipsychotic medication, we carried out a literature review. A systematic search strategy was performed using PubMed (Medline), Embase, PsychInfo, and Cochrane Database of Systematic Reviews. Publications describing adverse effects of antipsychotic medication in patients with 22q11.2DS were included in the review and assessed for their methodological quality. A total of 11 publications reporting on eight trials, cross‐sectional or cohort studies, and 30 case reports were included. The most commonly reported adverse effects can be classified into the following categories: movement disorders, weight gain, seizures, cardiac side effects, and cytopenias. Many of these symptoms are manifestations of 22q11.2DS, also in the absence of antipsychotic medication. Based on the reviewed literature, a causal relation between antipsychotic medication and the reported adverse effects could not be established in the majority of cases. Randomized clinical trials are needed to make firm conclusions regarding risk of adverse effects of antipsychotics in patients with 22q11.2DS.